From the Editors: Demystifying the Specialized Language Teaching (ESP) and Digital Technologies in Vocational Higher Education - ANAS, Ismail; TAMRIN, Tamrin (Research and Innovation in Applied Linguistics, 2023)
This journal is organized and published by UPT. Bahasa Politeknik Negeri Ujung Pandang and dedicated to contributing to the growth of applied linguistics studies. On behalf of the editorial board members, we are happy to announce and launch this first volume of Research and Innovation in Applied Linguistics-Electronic Journal (RIAL-EJ). This journal aims to publish scholarly articles in the area of applied linguistics, vocational English, and English for Specific Purposes (ESP), such as business English, English for engineering (mechanical, chemical, civil, and electrical engineering), English for health, and English for marine professionals. The central theme of this issue is â€œDemystifying the Specialized Language Teaching (ESP) and Digital Technologies in Vocational Higher Educationâ€ and the extent to which PBLL and the affordances of digital technology contribute to vocational English learning. In this volume, we publish five featured articles (3 research articles, one review article, and one interview article). The articles underwent several stages, including initial screening from the editorial board, blind review from two anonymous reviewers, multiple round revisions, proofreading, and copyediting process, plagiarism check with the iThenticate, and article production stage.